Minóicos: Os guardiães da primeira civilização europeia - Rui Morais (Ensino, 2019)
The work focuses on the First European Civilisation, that of the Minoans, beginning with a brief chronological introduction and its most significant discoveries in archaeology. In the following chapters, the main palatial complexes and other habitats are described, framed within the so-called Cretan Thalassocracy in the Aegean. The work continues with religion, discussing its cults and rituals, as well as the different writing systems found on small clay tablets (hieroglyphic, linear A and B) and the enigmatic Phaistos Disc. In appendix, some records of Minoan art are presented, namely painting, pottery, glyptic art, jewellery and sculpture, as well as other miniature works.